Keterampilan Konselor Dalam Menyusun Program Manajemen Bimbingan Dan Konseling - Yenti Arsini; Rebeca Yamani; Syifa Nurahma Saragih; Yuda Prasatya (CV. ITTC INDONESIA, 2023)
The purpose of this study was to determine the skills of conselors in preparing bimbing and conseling management programs. In guidance and counseling management, counselors have a leading role and significance regarding the success of guidance and counseling services. Counselors have an assignment and even responsibility for the level of quality and competence. In order to support the implementation of counseling, counselors are required to master counseling skills. In fact, the field also shows that counselors are still not all used for counseling services. The existence of a collection of skill characteristics underlying counseling will be required to be mastered from the counselor, but the study focuses on the skills to be carried out in the arrangement of guidance and counseling programming. This research uses a research method that is literature even research in the library (library research). From the explanation above, the research is about the implementation of counseling skills in the preparation of guidance and counseling programs. The study outlined the urgency of counseling skills that must be possessed by counselors in implementing guidance and counseling services.